Mode of Transport along the Quality Dimension - Esteban Jaimovich; Vincenzo Merella (Prague University of Economics and Business, Faculty of International Relations (FIR), 2021)
Aeroplanes are a fast but expensive means of shipping goods, which allow producers to respond quickly to favourable demand realisations and to limit the risk of shipping unproÖtably large quantities during low demand periods while substantially raising the transportation cost relative to ocean cargoes. We explore the role of heterogeneous income elasticity of demand faced by exporters of quality-differentiated goods in shaping the transport mode choice. We find that more considerable demand volatility induces more exporters to opt for air shipping, and more so if they produce high-quality goods. We also produce supporting evidence based on U.S. data at the exporter-district-product level.
Keywords: F1; F14; 330; International trade; Transportation mode; Unit values; PIGL utility function